Maternal Environment and the Transgenerational Cycle of Obesity and Diabetes - Dana Dabelea; Tessa Crume (2011)
he prevalence of obesity continues to increase worldwide and represents one of the most pressing public health issues due to its associated morbidity, mortality, and health care costs.Novel research is demonstrating that alterations of the maternal environment can impact the intrauterine development of the fetus and influence the offspring's risk for obesity and type 2 diabetes over the lifecourse.This article reviews the epidemiological evidence with a focus on the fetal overnutrition hypothesis.We discuss potential mechanisms and suggest future directions for research.